Recreational Harvesting of the Florida Bay Scallop: Wakulla County - Savanna Barry (EDIS)
This handy brochure includes a full-color map identifying access routes to the boat ramps and marinas in Wakulla County, plus the latest information on scallops and scalloping, the recommended equipment you will want to bring, and a few tasty recipes for preparing Florida’s best summertime catch. It is a minor revision written by Savanna Barry and published by the UF/IFAS Extension Florida Sea Grant College Program, June 2019.